ON NON-VERBAL COMMUNICATION AND ITS IMPORTANCE IN EDUCATION: (using the example of the Macedonian language as a foreign language) (Philological Studies, 2022)
Language is well known as a means of communication that covers both verbal and non-verbal communication, to which a large array of research has been devoted.In recent decades, attention has been paid to the methodology of learning a foreign language, which is advocated by the Council of Europe, especially after the publication of the Common European Framework of Reference (CEFR) for languages: learning, teaching, and assessment. CEFR has included the collected theoretical and practical experiences of: learning, teaching, and evaluating a language, accumulated from 1971 to 2001 (up to its publication). In the paper, we shall first refer to the phenomenon of non-verbal communication, then provide a review of nonverbal communication in the Common European Reference Framework. Finally, we shall focus on non-verbal communication when learning Macedonian as a foreign, non-native language, while also analyzing the implementation of skills in non-verbal communication (forms, means, different types: body language, images, colors, etc.).